Initial invasion of glyphosate‐resistant Amaranthus palmeri around grain‐import ports in Japan. Issue 6 (24th September 2020) - Shimono, Ayako; Kanbe, Hiroki; Nakamura, Shunta; Ueno, Saneyoshi; Yamashita, Jun; Asai, Motoaki
Societal Impact Statement: The dispersal of alien species is tightly coupled to human activities such as trade and transport. Trade is known to spread troublesome weeds from countries exporting, to those importing, grain. Glyphosate resistant (GR) Amaranthus palmeri is one of the most problematic weeds in the US, which is the largest grain exporter to Japan. We demonstrate that GR A. palmeri has become established in a Japanese port in less than 10 years from the first report of GR A. palmeri in the US. The initial detection of alien species is critical to enable effective control measures to be undertaken, before problematic species are able to spread more widely. Summary: The US is the largest source to Japan of crops genetically modified to be glyphosate resistant (GR). The intensive use of glyphosate in the US has led to the evolution of GR Amaranthus palmeri, one of the most problematic weeds in the US. Here, we investigated the initial invasion and establishment of GR A. palmeri at grain‐importing ports in Japan. The primary glyphosate resistance mechanism is a copy‐number amplification of the 297‐kb region containing the herbicide target site gene 5‐enolpyruvylshikimate‐3‐phosphate synthase ( EPSPS ). We used quantitative PCR to measure the EPSPS genomic copy number and used PCR to confirm the presence of the other amplified region. We used microsatellite marker analysis to compare the genetic similarities between Japanese populations and US accessions. We detected GR A. palmeri at three ports: although present as a casual plant at two of the three ports, GR populations were established at one of the ports investigated. The port populations were found to be genetically similar to the US accessions and showed no geographical genetic structure. This study shows that GR A. palmeri has naturalized in Japan in less than 10 years from the first report of GR A. palmeri in the US. Abstract : The dispersal of alien species is tightly coupled to human activities such as trade and transport. Trade is known to spread troublesome weeds from countries exporting, to those importing, grain. Glyphosate resistant (GR) Amaranthus palmeri is one of the most problematic weeds in the US, which is the largest grain exporter to Japan. We demonstrate that GR A. palmeri has become established in a Japanese port in less than 10 years from the first report of GR A. palmeri in the US. The initial detection of alien species is critical to enable effective control measures to be undertaken, before problematic species are able to spread more widely.